Description of Resilience in Students with Deceased Parents - Pah, Sesilia; Junias, Marylin Susanti; Panis, Marleny Purnamasari (Universitas Nusa Cendana, 2025)
Students who lose one or both parents face emotional and psychological challenges that can affect their resilience abilities. This study aims to describe how the level of resilience of students with deceased parents at Nusa Cendana University using a quantitative descriptive approach. The measuring instrument used in this study is the Connor-Davidson scale (CD-RISC). The results showed that on average, students with deceased parents had a level of resilience in the moderate category (70%). This finding indicates that despite facing pressure due to the loss of parents, most students are able to maintain a fairly good level of resilience. Further analysis revealed that academic performance, time span of parental loss, and involvement in organizations contributed to the level of resilience, with spiritual influence being the dominant factor. This study highlights the importance of social support and internal factors in building student resilience. The findings provide a basis for the development of interventions that support university students facing the challenges of parental loss.